PENGARUH HUTANG, KEPEMILIKAN SAHAM, DEWAN KOMISARIS DAN PROFITABILITAS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Rosdwiana Putri Dewi; Dirvi Surya Abbas; Imam Hidayat; Dewi Rachmania (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
This study aims to obtain empirical evidence of the influence of debt, share ownership, board of commissioners and profitability on disclosure of food and beverage company social responsibility on the IDX in 2015-2021. This study uses financial report data from food and beverage companies during the 2015-2021 period. As well as obtaining answers to the gaps in several previous research results. The analytical tool used to test the effect between variables in this study is a simultaneous test (f test) and partial test (t test) regarding each variable X on variable Y with a confidence level of 95%. Then from the partial test results using the t test. t test is known that debt, foreign share ownership, the board of commissioners and profitability have a significant effect on social responsibility. The entire analysis uses the e-views program. The results of this study are expected to provide an overview and understanding of corporate social responsibility disclosure.